The Physical, Chemical Properties of untreated and chemically treated Palmyra Palm Leaf Fibres - Thiruchitrambalam, M; Logesh, M; Shanmugam, D; Muthukumar, S (International Journal of Engineering and Technology, 2018)
Palmyra palm leafÂ fibre a natural fibre extracted from palmyra palm treeÂ Â was treated withÂ sodium hydroxide, benzoylchloride and potassium permanganate.Â Effects of these treatments on the changes in physical, chemical properties were determined experimentally. The density of the fibres was found to increase, while the diameter of fibres reduced due to treatments. The morphology of untreated and treated fibres were examined using Scanning electron microscope.